Effects of sintering temperature on microstructure and complex permittivity of magnesium titanate-doped barium strontium titanate prepared via mechanical alloying - Abdul Halim, Dayang Nur Fazliana (2018)
Uncovering the relationship between microstructure and dielectric properties is beneficial knowledge for finding high dielectric constant materials with low loss for technological purposes. Thus this research work attempts to understand the evolving relationship over sintering temperature between permittivity and microstructure properties in barium strontium titanate (BST), magnesium titanate (MT) and magnesium titanate doped barium strontium titanate (BST-MT). BST, MT and BST-MT samples were mechanically crush activated using a high energy ball mill for 10, 12 and 2 hours respectively. Pellets were formed followed by a sintering process from 500 oC up to 1300 oC with 100 oC increment. The phase analysis carried out using X-ray diffraction (XRD) showed a highly crystalline BST, MT or BST-MT ceramic could not be formed during milling alone. At 500 oC, the major reflection (Ba0.5Sr0.5TiO3, MgTiO3 or Ba0.5Sr0.5TiO3/MgTiO3) grew from a broad peak into a sharp peak as it reached 1300 oC. In BST-MT system, there was no trace of dopant, MgTiO3 observed in XRD for all sintering temperatures. However, the energy dispersive X-ray (EDX) images confirmed the presence of Mg ion in BST-MT system. Sintering activity showed an improvement in the density where it increased from 3.67 g/cm3 to 4.88 g/cm3 for BST samples, 3.08 g/cm3 to 3.56 g/cm3 for MT samples and from 3.914 g/cm3 to 5.318 g/cm3 BST-MT sample. Field emission scanning electron microscope (FESEM) presented the average starting particle sizes were 39 nm, 89 nm and 78 nm for BST, MT and BST-MT respectively. There were an improvement in the grain growth where the grain size increased from 32.9 nm to 174.8 nm for BST, 87.5 nm to 1575.0 nm for MT and 80.8 nm to 267.5 nm for BST-MT. The dielectric properties investigated using the Agilent 4294A Impedance analyzer revealed the dielectric constant, ԑr’ showed a decreasing trend below 104 HZ with increasing frequency for all samples due to the interfacial polarization. At 1 MHz, εr’ increased from 49.28 to 143.68 (BST), from 28.15 to 47.39 (MT) and from 46.52 to 120.81 (BST-MT) with the rise of sintering temperatures. Therefore it revealed the dependency of dipolar polarization on the grain size and the crystalline structure resulting in a remarkable increase in polarizability. The tangent loss was found to decrease with frequency where a high tan δ at low frequency due to the decrement of hopping process of ions. The Nyquist plot in all sample revealed the attribution to the grain property of the material with the rise of sintering temperature. Complex modulus revealed one semicircle observed for higher sintered BST and MT. However, the introduction of dopant caused two semicircle observed for BST-MT sintered at 1200 oC and 1300 oC at all measuring temperatures suggesting the presence of both the grain and grain boundary contribution in the sample. BST-MT samples sintered at 1200 oC showed a prominent candidate for energy storage application as it experience a good physical properties with dielectric constant of 97.9 and 65% lesser dielectric loss compared to pure BST.